2012
DOI: 10.1007/s10526-011-9437-8
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and harm caused by the introduced generalist tachinid, Compsilura concinnata, in North America

Abstract: We review North American research on Compsilura concinnata (Meigen), a highly generalist tachinid parasitoid that was introduced in 1906 to control two invasive forest insects: gypsy moth and browntail moth. The impact on gypsy moth in natural populations in North America has long thought to be minor, a view confirmed by recent work in Canada and Wisconsin, USA. However, research with experimentally created populations of gypsy moth suggests that it may be more important than previously realized. Studies on br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Here again, the actual introduction was considered successful but not effective, as C. synchophanta failed to control its target (Munroe 1971). Subsequent work has shown that C. concinnata, likely introduced to Canada during these early Tothill releases, is one of the main causes for collapse of browntail moth populations across eastern North America (Elkinton and Boettner 2012). The initiatives of Hewitt and Tothill greatly accelerated biological control in Canada, launching programmes against at least 12 targets between 1925and 1940 (Fig.…”
Section: The Early Era: 1882-1945mentioning
confidence: 99%
“…Here again, the actual introduction was considered successful but not effective, as C. synchophanta failed to control its target (Munroe 1971). Subsequent work has shown that C. concinnata, likely introduced to Canada during these early Tothill releases, is one of the main causes for collapse of browntail moth populations across eastern North America (Elkinton and Boettner 2012). The initiatives of Hewitt and Tothill greatly accelerated biological control in Canada, launching programmes against at least 12 targets between 1925and 1940 (Fig.…”
Section: The Early Era: 1882-1945mentioning
confidence: 99%
“…An example of this can be seen with C. concinnata. Evidence from the North American use of C. concinnata as an introduced biocontrol agent for gypsy and brown-tail moths suggests that this species also has a very wide host range (Strazanac et al 2001;Elkinton & Boettner 2012), and that it is generally ineffective at preventing the spread of the two main target species because of low parasitism levels. This species was also detected at very low levels in UK OPM, but whether these were accidental parasitism events caused by adult females misinterpreting oviposition cues or the first steps in the host range expansion of the UK race of C. concinnata is unclear.…”
Section: Opm Its Parasitoids and Ipmmentioning
confidence: 99%
“…But there are many exceptions. For example, the tachinid parasitoid Compsilura concinnata, introduced in North America against the gypsy moth, has more than 200 known hosts (Elkinton and Boettner 2012). On the other hand, successful predators such as the coccinellids Hyperaspis pantherina and Rodolia cardinalis, released against the orthezia scale in St Helena and against the cottony cushion scale in the Galapagos, respectively, or the beetle Rhizophagus grandis, released against the great spruce bark beetle (Dendroctonus micans) in Europe, are specific (Grégoire et al 1992;Van Driesche et al 2010;Cock et al 2015).…”
Section: Do Parasitoids and Predators Work Equally Well?mentioning
confidence: 99%